2020
DOI: 10.1111/hel.12695
|View full text |Cite
|
Sign up to set email alerts
|

Gastric microbiota and Helicobacter pylori in Indonesian population

Abstract: Background:The profile of gastric mucosal microbiota has not yet been described in the Indonesian population where the prevalence of Helicobacter pylori is low.Methods: This is a cross-sectional study analyzing 16S rRNA of 137 gastric biopsy specimens. We analyzed the association between gastric microbiota, H. pylori infection, and gastric mucosal damage.Result: Among 137 analyzed samples, 27 were H. pylori-positive and 110 were H. pylori -negative based on culture, histology, and 16S rRNA gene analysis. Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…Previous studies have demonstrated that H. pylori infection is associated with marked changes in the gastric microbiota [14,19,[22][23][24]. Here, we confirmed that H. pylori-negative and -positive patients had different bacterial profiles characterized by less richness of gastric microbiota and the reduction in abundances of Blautia, Ralstonia, Faecalibacterium, Methylobacterium, and Megamonas in H. pylori-positive patients.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have demonstrated that H. pylori infection is associated with marked changes in the gastric microbiota [14,19,[22][23][24]. Here, we confirmed that H. pylori-negative and -positive patients had different bacterial profiles characterized by less richness of gastric microbiota and the reduction in abundances of Blautia, Ralstonia, Faecalibacterium, Methylobacterium, and Megamonas in H. pylori-positive patients.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the role of baseline demographic characteristics remained to be elucidated in future studies. The compositional analysis showed that H pylori frequently dominated the gastric mucosa of infected individuals while other phyla, including Actinobacteria , Bacteroidetes , Firmicutes , and Fusobacteria, tended to become relatively low 6,19,20,22‐25 . In contrast, gastric microbiota of noninfected samples were found to be enriched with Streptococcus 6,22,23 .…”
Section: Gastrointestinal Microbiota Reshaping Upon H Pylori Infectionmentioning
confidence: 96%
“…The phenomenon could be attributed to the harsh environment at the end stage since H pylori itself was sharply reduced through gastric carcinogenesis 26 . Most studies revealed that individuals infected with H pylori had distinct community structures compared with H pylori ‐negative counterparts 19‐23,25,27 . However, in two earlier studies, neither alpha diversity nor community structures were found to be different between H pylori ‐positive and H pylori‐ negative groups 4,28 .…”
Section: Gastrointestinal Microbiota Reshaping Upon H Pylori Infectionmentioning
confidence: 97%
See 1 more Smart Citation
“…Gastric microbiota sequencing studies have reported Firmicutes, Proteobacteria, Actinobacteria, Bacteroidetes, and Fusobacteria phyla colonization [ 5 , 6 ]. This microbiota variability is multifactorial and associated with diet, drugs, antibiotics, immune response, chronic processes, and H. pylori infections [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%